(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the degree of satisfaction of users in chronic conditions who use biological therapy in a secondary health care service. Method: Quantitative, descriptive and exploratory research, carried out in a Polyclinic of the State of Rio de Janeiro, in the months of November and December 2017, with 70 users with chronic conditions monitored in the specialties of rheumatology, gastroenterology, allergy and pneumology that make use of biological therapy. A questionnaire with variables related to the characteristics of users and satisfaction with the service was used. Results: Users evaluated the service as satisfactory in terms of reception, care from the nursing and health team, as well as feeling feelings of security and trust in the team during the service. Conclusion: the evaluation proved to be positive in the different dimensions, which enables decision making, based on the knowledge of the service’s performance under the user’s view. An excellent degree of user satisfaction promotes motivation of the professionals who assist them and allows the manager to create strategies for continuity and improvements in the processes aimed at welcoming and assisting these subjects.